High-temperature-resistant and high-humidity-resistant polyurethane hot melt adhesive PUR and preparation method thereof
Through the synergistic effect of components such as hexagonal boron nitride nanosheets, the stability problem of polyurethane hot melt adhesive in high temperature and high humidity environments is solved, the thermal conductivity and water resistance of the adhesive layer and the protection of the molecular chain are achieved, and the reliability of electronic equipment is improved.
Patent Information
- Application Number
- CN202511166809.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-20
- Publication Date
- 2025-10-21
- Estimated Expiration
- 2045-08-20
AI Technical Summary
Traditional polyurethane hot melt adhesives cannot maintain stability simultaneously in high temperature and high humidity environments, leading to reliability issues in electronic equipment.
By adopting the synergistic effect of components such as hexagonal boron nitride nanosheets, nano-silica, hydrazide-based capture agents, heat-activated microsphere epoxy resins and zirconium aluminate, through vertical magnetic field orientation and multi-stage curing treatment, a heat-conducting, water-blocking and repairing structure is formed to enhance the high temperature and high humidity resistance of the adhesive layer.
It effectively blocks the penetration of water molecules, prevents the softening of the adhesive layer and the hydrolysis of the molecular chain, improves the high temperature and high humidity resistance of electronic equipment packaging, and ensures the stability of the adhesive layer in high temperature and high humidity environments.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic packaging, and in particular to a high-temperature and high-humidity resistant polyurethane hot melt adhesive (PUR) and a preparation method thereof. Background Art
[0002] As electronic devices advance towards higher performance and miniaturization, their operating temperature and humidity environments are becoming increasingly stringent. For example, automotive electronics must withstand the dual challenges of temperatures of 85°C and 85% relative humidity for extended periods of time. Heat-generating components like 5G chips can reach surface temperatures exceeding 100°C. Polyurethane hot-melt adhesive (PUR) is widely used in electronic packaging due to its flexibility and ease of processing. However, the stability of traditional PUR in high-temperature, high-humidity environments has become a key bottleneck restricting device reliability.
[0003] At present, PUR's high temperature resistance or high humidity resistance can be unilaterally improved through modification, but the two cannot be achieved at the same time. The reason is that improving heat resistance requires increasing the cross-linking density or introducing rigid chain segments, but this will reduce the mobility of the molecular chain, forcing moisture to diffuse linearly along the rigid interface, which will accelerate hydrolysis; while improving moisture resistance depends on hydrophobic groups, which will weaken the interfacial adhesion between the adhesive layer and the metal / plastic substrate under high temperature conditions.
[0004] Therefore, it is necessary to provide a new polyurethane hot melt adhesive that can inhibit high-temperature softening and block water molecule penetration. Summary of the Invention
[0005] In view of this, the present application provides a high-temperature and high-humidity resistant polyurethane hot melt adhesive PUR and a preparation method thereof, which are used to solve the problem of how to simultaneously improve the high-temperature resistance and high-humidity resistance of the polyurethane hot melt adhesive PUR.
[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions: In a first aspect, the present invention provides a high-temperature and high-humidity resistant polyurethane hot melt adhesive PUR, comprising the following components in parts by mass: 80-100 parts of polyether polyurethane particles, 5-8 parts of hexagonal boron nitride nanosheets, 1-3 parts of hollow nano-silica, 3-5 parts of hydrazide-based capture agents, 1-2 parts of heat-activated microsphere epoxy resin, 0.5-1 part of zirconium aluminate, and 5-10 parts of hydrogenated terpene resin.
[0007] Preferably, the softening temperature of the heat-activated microsphere epoxy resin is 95-114°C.
[0008] Preferably, the hydrazide-based capturing agent is sebacic acid dihydrazide.
[0009] Preferably, the mass ratio of sebacic acid dihydrazide to heat-activated microsphere epoxy resin is 1.5-2.5:1.
[0010] Preferably, the molar ratio of Zr element to Al element in the zirconium aluminate nanoclusters is 2-4:1.
[0011] In a second aspect, the present application provides a method for preparing a high temperature and high humidity resistant polyurethane hot melt adhesive (PUR), comprising the following steps: S1. The polyether polyurethane particles are mixed with the hydrogenated terpene resin after vacuum dehydration to obtain a dehydrated matrix; S2. Adding boron nitride nanosheets and hollow nano-silica to the dehydrated matrix, and then shearing it under a perpendicular magnetic field to obtain a magnetically oriented composite; S3. At a certain temperature, zirconium aluminate is added to the magnetically oriented composite and dispersed evenly. Then, a hydrazide-based scavenger and a heat-activated microsphere epoxy resin are added and mixed and extruded to obtain a high-temperature and high-humidity resistant polyurethane hot melt adhesive (PUR).
[0012] Preferably, in step S2, shearing is performed at 500 rpm for 20 min in a 0.5-1 T vertical magnetic field.
[0013] Preferably, in step S3, the temperature is 70-80°C.
[0014] In a third aspect, the present application provides a method for applying a high-temperature and high-humidity resistant polyurethane hot melt adhesive PUR. After application, the adhesive is cured at 80-90°C for 20 minutes, 95-114°C for 10 minutes, and 60-80°C for 24 hours.
[0015] In a fourth aspect, the present application provides an application of a high-temperature and high-humidity resistant polyurethane hot melt adhesive PUR in the preparation of electronic device packaging.
[0016] The beneficial effects of the present application are as follows: the present application solves the problem of softening and failure of the adhesive layer due to high temperature by combining the rapid thermal conductivity of boron nitride with the high-temperature repair of epoxy microspheres; solves the problem of hydrolysis and fall-off of molecular chains caused by high humidity by combining the lateral water barrier of boron nitride with the water absorption of silica and the blocking of hydrolysis by hydrazide; and utilizes the synergistic effect of multiple components to solve the problem of softening and failure of the adhesive layer due to high temperature and hydrolysis and fall-off of molecular chains caused by high humidity in electronic equipment packaging. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0018] The invention provides a high-temperature and high-humidity resistant polyurethane hot melt adhesive (PUR), which comprises the following components in parts by mass: 80-100 parts of polyether polyurethane particles, 5-8 parts of hexagonal boron nitride nanosheets, 1-3 parts of hollow nano-silica, 3-5 parts of hydrazide-based capturing agents, 1-2 parts of heat-activated microsphere epoxy resin, 0.5-1 part of zirconium aluminate, and 5-10 parts of hydrogenated terpene resin.
[0019] In this application, polyether-type polyurethane particles are used as the matrix material. The ether bonds in their molecular chains possess excellent flexibility and hydrolysis resistance. Their long molecular chains act like an "elastic net" enveloping other components (for example, TPU chains adsorb to the h-BN surface via van der Waals forces, forming a "wrapped-wrapped" structure), buffering thermal stress during temperature fluctuations. However, pure polyurethane softens and fails at high temperatures. In humid environments, ester bonds readily hydrolyze upon contact with water. Water molecules attack the ester bonds, forming carboxyl groups, which further catalyze the cleavage of surrounding ester bonds, forming a chain reaction (autocatalytic hydrolysis), ultimately causing the adhesive layer to pulverize and fall off. Therefore, this application introduces hexagonal boron nitride nanosheets, which form a unique "standing" arrangement when exposed to a perpendicular magnetic field. This structure not only rapidly conducts heat vertically to dissipate heat from the chip, preventing heat accumulation and softening of the adhesive layer, thereby addressing the high-temperature softening issue, but also forces water molecules to take a long detour horizontally, preventing water vapor penetration, thereby addressing the moisture issue.
[0020] The porous structure inside the nano-silica of the present application absorbs the infiltrated water molecules, expands itself to fill the gaps, locks in moisture, blocks water molecules from attacking the molecular chains of the adhesive layer, enhances the structural strength of the polyurethane hot melt adhesive, and alleviates the disadvantage of easy hydrolysis under high humidity and high heat conditions.
[0021] As those skilled in the art know, the humid environments of electronic devices often contain acidic substances, which can catalyze the breakage of polyurethane molecular chains and produce -COOH. At the same time, the acidic fragments further accelerate the hydrolysis of the material, forming a vicious cycle. The hydrazide-based capture agent in this application is more active than water molecules and can preemptively capture -COOH to block the hydrolysis chain reaction. The heat-activated epoxy microspheres (compared to non-heat-activated epoxy microspheres, which require heating to trigger the curing reaction) soften at a critical temperature (95-114°C), releasing epoxy groups, which react with hydrazide groups to form new crosslinking points. The hydrolysis byproduct -COOH is then used to repair the damaged molecular chains.
[0022] The zirconium aluminate of the present application can form a dense passivation film to prevent chloride ions in sweat or salt mist from corroding the circuit, further improving the high temperature and high humidity resistance.
[0023] This application solves the problem of softening and failure of the adhesive layer due to high temperature by combining the rapid thermal conductivity of boron nitride with the high-temperature repair of epoxy microspheres. It solves the problem of hydrolysis and detachment of molecular chains caused by high humidity by combining the lateral water barrier of boron nitride with the water absorption of silica and the blocking of hydrolysis by hydrazide. It utilizes the synergistic effect of multiple components to solve the problem of electronic equipment packaging being intolerant to moisture under high temperature conditions and intolerant to high temperature under high humidity conditions.
[0024] In some embodiments, the heat activated microsphere epoxy resin has a softening temperature of 95-114°C.
[0025] In this embodiment, if the softening point is too low, epoxy is released during the mixing stage, causing the rubber compound to be prematurely cross-linked and scrapped; if it is too high, repair is delayed and the electronic components are damaged by overheating.
[0026] In some embodiments, the hydrazide-based capture agent is sebacic acid dihydrazide.
[0027] In some embodiments, the mass ratio of sebacic acid dihydrazide to heat-activated microsphere epoxy resin is 1.5-2.5:1.
[0028] In this embodiment, if the amount of hydrazide is too little, not all carboxyl groups can be captured, and the residual acid accelerates hydrolysis; if the amount of hydrazide is too much, excessive cross-linking will occur, making the adhesive layer brittle.
[0029] In some embodiments, the molar ratio of Zr to Al in the zirconium aluminate nanoclusters is 2-4:1.
[0030] In this embodiment, too high or too low a ratio of zirconium to aluminum may reduce the density of the passivation film.
[0031] The present application provides a method for preparing a high-temperature and high-humidity resistant polyurethane hot melt adhesive (PUR), comprising the following steps: S1. The polyether polyurethane particles are mixed with the hydrogenated terpene resin after vacuum dehydration to obtain a dehydrated matrix; S2. Adding boron nitride nanosheets and hollow nano-silica to the dehydrated matrix, and then shearing it under a perpendicular magnetic field to obtain a magnetically oriented composite; S3. At a certain temperature, zirconium aluminate is added to the magnetically oriented composite and dispersed evenly. Then, a hydrazide-based scavenger and a heat-activated microsphere epoxy resin are added and mixed and extruded to obtain a high-temperature and high-humidity resistant polyurethane hot melt adhesive (PUR).
[0032] In some embodiments, in step S2, shearing is performed at 500 rpm for 20 min in a 0.5-1 T perpendicular magnetic field.
[0033] In this embodiment, boron nitride rotates due to the Lorentz force due to its anti-magnetism. After shearing treatment, it can ensure that the boron nitride nanosheets are vertically oriented, which not only optimizes the thermal conductivity and water resistance, but also avoids the stress concentration problem caused by filler agglomeration.
[0034] In some embodiments, in step S3, the temperature is 70-80°C.
[0035] In this embodiment, if the mixing temperature is too low, uneven dispersion of the components will result, while if the mixing temperature is too high, premature activation of the epoxy microspheres will occur.
[0036] The present application provides a method for applying a high-temperature and high-humidity resistant polyurethane hot melt adhesive (PUR), which is sequentially cured at 80-90°C for 20 minutes, 95-114°C for 10 minutes, and 60-80°C for 24 hours after application.
[0037] In this application, the polyurethane molecular chains are first induced to arrange in an orderly manner at 80-90°C to form initial physical cross-linking points; the temperature is then raised to 95-114°C to trigger the repair function of the epoxy microspheres (the curing temperature of the second stage is the same as the softening temperature of the epoxy microspheres), repairing the breakage points of the molecular chains; finally, the temperature is maintained at 60-80°C for 24 hours to allow sufficient time for the zirconium aluminate to migrate to the metal interface to form a complete protective film.
[0038] The present application provides an application of a high-temperature and high-humidity resistant polyurethane hot melt adhesive (PUR) in the preparation of electronic equipment packaging.
[0039] Source of raw materials: Hexagonal boron nitride nanosheets: Xi'an Qiyue Biotechnology Co., Ltd., catalog number 52352; Heat-activated microsphere epoxy resin: Guangzhou Zhuocen Chemical Co., Ltd., DER 6508 (softening point 95-105°C) or DER 6510HT (105-114°C); Non-heat-activated microsphere epoxy resin: Guangzhou Zhuocen Chemical Co., Ltd., DER 6615 (softening point 78-86°C); Hollow nano-silica: Xi'an Ruixi Biological, 100-300nm.
[0040] The present invention is further described below through specific examples. Example
[0041] A high-temperature and high-humidity resistant polyurethane hot-melt adhesive (PUR) comprises the following components in parts by mass: 90 parts of polyether polyurethane particles, 6 parts of hexagonal boron nitride nanosheets, 2 parts of hollow nano-silica, 4 parts of sebacic acid dihydrazide, 1.5 parts of heat-activated microsphere epoxy resin, 0.8 parts of zirconium aluminate, and 5 parts of hydrogenated terpene resin; the softening temperature of the heat-activated microsphere epoxy resin is 95-114°C.
[0042] The preparation method of high temperature and high humidity resistant polyurethane hot melt adhesive PUR comprises the following steps: S1. 90 parts of polyether polyurethane pellets and 5 parts of hydrogenated terpene resin were added to a twin-screw extruder with an aspect ratio of 40:1 and a temperature of 80°C. The mixture was mixed and melted under a vacuum of -0.095 MPa for 2 hours to ensure a moisture content of <0.02%. The melt was water-cooled and pelletized to obtain uniform dehydrated matrix pellets, which were then sealed and stored for later use. S2. The dehydrated matrix particles were added to an internal mixer and melted at 75°C and 50 rpm. Six parts of hexagonal boron nitride nanosheets were added and mixed at 100 rpm for 5 minutes to prevent agglomeration. Two parts of nano-silica were then added and mixed for 10 minutes to ensure uniform dispersion. The mixture was then transferred to a magnetic field shearing device equipped with a NdFeB permanent magnet with a magnetic field strength of 0.8 T and treated at a shear rate of 500 rpm for 20 minutes to vertically align the boron nitride nanosheets. S3. Transfer the magnetically oriented composite to a planetary mixer, add 0.8 parts of zirconium aluminate nanoclusters at a temperature of 75°C and a vacuum of -0.09 MPa, stir for 15 minutes until completely dispersed, then add 4 parts of sebacic acid dihydrazide, stir for 10 minutes, and finally add 1.5 parts of heat-activated epoxy microspheres, stir at 50 rpm for 5 minutes to prevent the microspheres from breaking. After mixing evenly, extrude into strips through a single-screw extruder at a temperature of 80°C and a die pressure of 5 MPa, water-cooled and pelletized to obtain the final hot melt adhesive product.
[0043] The application method of the high temperature and high humidity resistant polyurethane hot melt adhesive PUR is as follows: heat the hot melt adhesive particles to 85°C to melt, apply them to the electronic device packaging part (thickness 0.2mm), and cure them using the following procedure: 85°C for 20 minutes, 114°C for 10 minutes, and 70°C for 24 hours.
[0044] Examples 2-5 A high temperature and high humidity resistant polyurethane hot melt adhesive (PUR), the other contents of which are the same as those in Example 1, except that the amounts of hexagonal boron nitride nanosheets are 3, 5, 8, and 10 parts, respectively.
[0045] Comparative Example 1 A polyurethane hot melt adhesive PUR, other contents are the same as those in Example 1, except that the magnetic field is canceled in step S2.
[0046] Comparative Example 2 A polyurethane hot melt adhesive PUR, other contents are the same as those in Example 1, except that the heat-activated microsphere epoxy resin is replaced by non-heat-activated microsphere epoxy resin.
[0047] Comparative Example 3 A polyurethane hot melt adhesive PUR, other contents are the same as those in Example 1, except that the amount of sebacic acid dihydrazide is 1.5 parts.
[0048] Comparative Example 4 A polyurethane hot melt adhesive PUR, other contents are the same as those in Example 1, except that the curing step of curing at 70° C. for 24 hours is omitted.
[0049] Testing and Evaluation The high humidity and high temperature resistance of the polyurethane hot melt adhesive PUR of different embodiments and comparative examples were tested. The test method is as follows: High temperature creep resistance: Apply a constant stress of 0.2 MPa at 85°C and record the strain rate (%) after 100 hours to evaluate the impact of high temperature conditions on the material; Hygrothermal aging: Testing the interface bond strength attenuation rate at 85°C / 85% RH (measured every 24 hours for a total of 168 hours) to evaluate the effects of high temperature and high humidity on the material's bonding performance. Water vapor permeability: measured at 38°C / 90% RH (ASTM E96), measured in g·mm / (m²·day), to assess the effects of high humidity conditions on materials.
[0050] The results are shown in Table 1.
[0051] Table 1 Test results ; Examples 1-5 show that the vertically arranged structure of boron nitride effectively enhances high-temperature rigidity, and the water vapor permeability decreases with increasing boron nitride content; Comparative Example 1 shows that disordered boron nitride completely loses its water-blocking ability and its high-temperature modulus drops sharply; Comparative Example 2 shows that unactivated epoxy microspheres cannot be dynamically repaired and their hydrolysis resistance decreases; Comparative Example 3 shows that insufficient hydrazide and residual carboxyl groups lead to local hydrolysis channels, resulting in poor resistance to high humidity and high temperature.
[0052] This application solves the problem of softening and failure of the adhesive layer due to high temperature by combining the rapid thermal conductivity of boron nitride with the high-temperature repair of epoxy microspheres. It solves the problem of hydrolysis and detachment of molecular chains caused by high humidity by combining the lateral water barrier of boron nitride with the water absorption of silica and the blocking of hydrolysis by hydrazide. It utilizes the synergistic effect of multiple components to solve the problem of electronic equipment packaging being intolerant to moisture under high temperature conditions and intolerant to high temperature under high humidity conditions.
[0053] The above are only preferred specific embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or replacements that can be easily thought of by any technician familiar with this technical field within the technical scope disclosed by the present invention should be covered by the scope of protection of the present invention.
Claims
1. A high temperature and high humidity resistant polyurethane hot melt adhesive PUR, characterized in that: The invention comprises the following components in parts by mass: 80-100 parts of polyether polyurethane particles, 5-8 parts of hexagonal boron nitride nanosheets, 1-3 parts of hollow nano-silica, 3-5 parts of hydrazide-based capturing agents, 1-2 parts of heat-activated microsphere epoxy resins, 0.5-1 parts of zirconium aluminate, and 5-10 parts of hydrogenated terpene resins.
2. The high temperature and high humidity resistant polyurethane hot melt adhesive PUR according to claim 1, characterized in that: The softening temperature of the heat-activated microsphere epoxy resin is 95-114°C.
3. The high temperature and high humidity resistant polyurethane hot melt adhesive PUR according to claim 1, characterized in that: The hydrazide-based capturing agent is sebacic acid dihydrazide.
4. The high temperature and high humidity resistant polyurethane hot melt adhesive PUR according to claim 1, characterized in that: The mass ratio of the hydrazide-based capturing agent to the heat-activated microsphere epoxy resin is 1.5-2.5:
1.
5. The high temperature and high humidity resistant polyurethane hot melt adhesive PUR according to claim 1, characterized in that: The molar ratio of Zr element to Al element in the zirconium aluminate nanoclusters is 2-4:
1.
6. A method for preparing the high temperature and high humidity resistant polyurethane hot melt adhesive (PUR) according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. The polyether polyurethane particles are mixed with the hydrogenated terpene resin after vacuum dehydration to obtain a dehydrated matrix; S2. Adding boron nitride nanosheets and hollow nano-silica to the dehydrated matrix, and then shearing under a perpendicular magnetic field to obtain a magnetically oriented composite; S3. At a certain temperature, zirconium aluminate is added to the magnetically oriented composite and dispersed evenly, and then a hydrazide-based capture agent and a heat-activated microsphere epoxy resin are added and mixed and extruded to obtain the high-temperature and high-humidity resistant polyurethane hot melt adhesive PUR.
7. The method for preparing the high temperature and high humidity resistant polyurethane hot melt adhesive PUR according to claim 6, characterized in that: In step S2, shearing was performed at 500 rpm for 20 min in a 0.5-1 T perpendicular magnetic field.
8. A method for preparing a high temperature and high humidity resistant polyurethane hot melt adhesive PUR, characterized in that: In step S3, the temperature is 70-80°C.
9. A method for applying the high temperature and high humidity resistant polyurethane hot melt adhesive (PUR) according to any one of claims 1 to 5, characterized in that: After applying the glue, cure at 80-90℃ for 20 minutes, 95-114℃ for 10 minutes, and 60-80℃ for 24 hours.
10. Use of the high temperature and high humidity resistant polyurethane hot melt adhesive (PUR) according to any one of claims 1 to 5 in preparing electronic device packaging.
Citation Information
Patent Citations
Hot melt adhesive film for vehicle FFC wire rod and preparation method of hot melt adhesive film
CN117659886A
High-temperature-resistant and high-humidity-resistant PUR hot melt adhesive and preparation method thereof
CN120082315A
Two-component polyurethane pouring sealant and preparation method thereof
CN120484756A
Thermoconductive sheet
JP2002080617A
Heat conductive adhesive film and manufacturing method thereof and electronic component
US20020050585A1